BoschDoc - Bosch Research and Conservation Project; Radboud Universiteit Nijmegen; Stadsarchief Herzogenbusch; Huygens Instituut (2016)
[Dt.:] In der Datenbank sind historische Dokumente zusammengefasst, die Inhalte zu Hieronymus Bosch und seinem Umfeld enthalten. Die Datensätze beinhalten ein digitales Faksimile und eine Transkription. In den Metadaten sind Informationen zur Entstehung und Provenienz enthalten. - [Engl.:] This database contains circa 1000 written documents about Hieronymus Bosch, his closest family, his life and his works. The documents in BoschDoc can be searched in two ways. There is the possibility of using any desired search term. You can also browse the various documents in BoschDoc. There are various categories in which the documents in BoschDoc are organised. For example, place of storage, period of origin, involved persons, and so on. You can narrow down your browse options. There is a facsimile, transcription and a translation included for every document.